If your answers match mine:
Remember to follow PEMDAS and 'what you do to one side [ because of equal sign] you do to the other'
11) 3n - 8 = 4
3n - 8 (+8) = 4 (+8)
3n = 12
3n/3 = 12/3
n = 4
12) 2n - 3 = 9
2n - 3 (+3) = 9 (+3)
2n = 12
2n/2 = 12/2
n = 6
13) n/5 -4 = 11
n/5 - 4 (+4) = 11 (+4)
n/5 = 15
n/5(5) = 15(5)
n = 75
14) z/2 + 1 = 9
z/2 + 1 (-1) = 9 (-1)
z/2 = 8
z/2(2) = 8(2)
z = 16
15) 2y + 16 = 10
2y + 16 (-16) = 10 (-16)
2y = -6
2y/2 = -6/2
y = -3
16) 3n + 2 = 12
3n + 2 (-2) = 12 (-2)
3n = 10
3n/3 = 10/3
n = 10/3 or 3.33 (repeating)
hope this helps